A bottom-up approach to estimating emissions from food systems: Using Biennial Transparency Reports for fine- grained, country-level estimations - Pingault, N.; Martius, C. (CIFOR-ICRAF, 2025)
Estimating greenhouse gas emissions from food systems remains a major challenge due to the lack of harmonized, sector-specific data that capture their cross-cutting nature. Food systems span all economic sectors along which national GHG inventories are usually structured: energy, industry, agriculture, land use and waste. However, national inventories are not fine-grained enough to disaggregate the share of food in those emissions, obscuring their full contribution and hindering integrated mitigation planning. Reliable, up-to-date country-level data are scarce, and global databases rely heavily on top-down estimates and outdated assumptions. To address this gap, we introduce a model estimating food system emissions (FSE) in Common Reporting Tables (CRT). The FSE-CRT model is a straightforward, transparent and bottom-up approach that draws exclusively on official national data, as reported by countries to the United Nations Framework Convention on Climate Change (UNFCCC) through their Biennial Transparency Reports (BTRs) and CRTs. It offers a credible alternative to global datasets that is grounded in nationally generated data that countries can control and validate (data sovereignty), and aligned with their priorities for food security and self-determined reporting.